Prospective audit on fasting status of elective ambulatory surgery patients, correlated to gastric ultrasound. Issue 1 (2nd January 2023) - Degeeter, Thibo; Demey, Birgit; Van Caelenberg, Els; De Baerdemaeker, Luc; Coppens, Marc
Abstract: Introduction: Recent guidelines advocate a preoperative fasting interval of 6 h for solid food, 4 h for breast milk and 2 h for clear fluids. Long nil per mouth intervals give rise to complications and discomfort in the perioperative period. Gastric ultrasound is easily accessible and generates reliable information about gastric content. Patients and methods: One hundred patients were offered a questionnaire regarding preoperative fasting. Important outcome measures were hour of last meal, last clear fluids intake, the source of preoperative information. Gastric ultrasound was performed in prone position and lateral decubitus. Results: The mean duration of fasting for solid food was 13h29 and 9h51 for clear fluids. 48% of patients were well aware of the correct fasting guidelines. The most frequent source of information was the preoperative phone call. Gastric ultrasound only found insignificant amounts of gastric content. Discussion: Too few patients are aware of the correct guidelines or fear complications and therefore adhere to the nil per mouth from midnight as most conservative measure. A phone call informing patients about the hour of surgery and allowing clear fluid intake until 2 h before surgery, is still not convincing enough. Some health care providers advise their patients the nil per mouth from midnight rule, due to risk of interfering with the operating room schedule. Conclusion: It is still difficult to implement liberal intake of clear fluids according to current guidelines. Ambulatory surgery patients have long fasting intervals with decrease of subjective well-being and increased incidence of hunger and thirst.